Marine Recreation Valuation: A Review - Jayaratne, Chamathi; Gunawardena, Prasanthi (Journal of Environmental Management and Tourism; Vol 17 No 2 (2026): JEMT, Volume XVII, Issue 2(82), Summer 2026DO - 10.14505/jemt.v17.2(82).04, 2026)
Marine and coastal ecosystems are main tourist attractions around the world. Being public goods, they are constantly become subjected to degradation. Estimation of economic values and proper appropriation of such values is a necessary requirement for their conservation and management. This study intends to review economic valuation studies on marine and coastal recreational areas with a view to identify trends and gaps and to formulate a research agenda towards sustainable management of the resource. Published literatures were explored with keywords such as marine, recreation and valuation using mainly google scholar and other search engines such as Science direct and individual journal web sites. The values of the studies were established in common currency unit of US$ and converted into 2026 prices using GDP deflator values. Results indicate diverse valuation approaches adopted and the variety of types of values that have been estimated. Both local and global focus were common and conceptual frameworks of total economic value and ecosystem service concepts have been equally adopted. All major ecosystems and their components and variety of uses have been the focus of the valuation studies. The adoption of values in the policy context however was rarely sought. The diversity of the valuation studies was lesser among the developing countries. The upcoming global threats such as climate change and the common resource degradations issues have not been adequately understood by the valuation studies. Towards the future, the trade-offs between the different ecosystem services as well as the synergies need to be correctly identified in order to minimize the conflicts among different user groups of the marine resources. The essentially global nature of the marine resources has to be correctly established to avoid future climate change related grand depletion of the resource. The complex dynamics of the ocean resources and increasing anthropogenic threats have to be understood with more interdisciplinary research and at least all key ecosystems have to have their baseline values established in the face of the rapid degradation due to increasing incidence of marine oil spills and unprecedented levels of other anthropogenic threats.